Prefabrik Sanayi Yapılarında Kullanılan Düşey Cephe Panellerinin Mesnetlenmesi İçin Bir Öneri - Aksakal, Tuğba (Fen Bilimleri Enstitüsü, 2013)
Bu çalışmada, prefabrik yapıların taşıyıcı sistemlerinden ziyade, yapının cephesini oluşturan düşey öndöküm paneller ve panellerin birleşim ve bağlantıları incelenmiştir. Yapılan çalışmalar sonucunda alternatif çözümler ortaya konmuştur. Tez kapsamında öndöküm cephe panellerinin davranışlarının doğrusal olmayan yöntemlerle incelenmesi için 2 farklı yol izlenmiştir. Birinci yaklaşımda, öndöküm cephe panellerinin gövdesinde 2 farklı biçimde boşluk oluşturulan sistemler ile dolu gövdeli sistemlerin, seçilen depremlerin etkisinde tükettikleri çevrimsel enerjiler karşılaştırılmıştır. Dolu gövdeli panel kullanmak yerine, gövdesinde farklı boyutlarda boşluklar oluşturularak, panelin daha sünek davranış yapması ve daha fazla enerji tüketmesi sağlanabilmektedir. İkinci yaklaşımda ise, öndöküm cephe panellerinin dış ortama enerji sönümleyici elemanlar ile bağlandığı durumdaki davranışları incelenmiştir. Öndöküm düşey cephe panellerinin temele, taşıyıcı yapı sistemine ve komşu panelle olan çeşitli bağlantı biçimleri incelenmiştir. Sünek panel bağlantı elemanları, deprem esnasında tüm yapı sisteminin enerji tüketimine büyük katkı sağlayabilmektedir.

This M.Sc. Thesis aims to evaluate the effectiveness of the new supporting system for vertical reinforced concrete precast cladding panels which are covering the industrial structures. The steel cushion for supporting of the cladding panel has been studied and some obtained promising results are presented. Two groups of analytical works have been performed in the content of this thesis. In the first group, the hysteretic behavior of three shear walls is compared with each other. Two different slit configurations have been tried for two specimens. The third specimen is the solid system. The results of nonlinear time history analyses are used to determine the dissipated hysteretic energy capacities of the structures. Depending on the results, it is easy to see that the creating slits on the web of the panels supplies more ductile behavior of the panels and then to gain much more capacity of energy dissipation. In the second group, the behavior of the cladding panels supported with the steel cushion is studied through the nonlinear time history analyses. The connections between cladding and foundation, the connections between load bearing system to claddings and cladding connections are the interested connection types. The steel cushion placed properly can supply great amount of energy dissipation of the whole structure studied in this work.
A New Proposal For The Supporting Of Vertical Reinforced Concrete Cladding Panels Used In Prefabricated Industrial Buildings
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Prefabrik yapı sistemleri; Cephe panelleri; Enerji tüketimi; Prefabricated industrial buildings; Cladding panels; Energy dissipation